Discovering Variables of Acculturation for Sojourners: An Explorative Study of Indonesian Students Living in Germany - Yuniarti, Kwartarini W. (Faculty of Psychology, Universitas Surabaya, 2010)
Sojourners are those who live in another culture for a period of time, with the intention of returning to their native land. Sojourning students have to adapt to a different culture and experience stresses due to acculturation. Most of the acculturation studies were about Chinese, Korean, or Japanese in the USA or foreign students other than Indonesians. No information was available on the signifi- cant variables of acculturation for Indonesian sojourning in Germany. This study aimed to explore variables of acculturation of Indonesian students in Germany, using qualitative approach. Results showed the following variables to be significant: (1) seasons and weathers, (2) living place, (3) cur- rent social relationship, (4) togetherness with Indonesians in Germany, (5) language, (6) the roles of work or academic environment, and (7) freedom. Details are discussed in this article. Sojourner adalah mereka yang hidup di luar negeri yang natinya akan pulang lagi ke tanah air. Mahasiswa di luar negeri termasuk dalam kelompok sojourner. Mahasiswa yang juga sojourner di luar negeri tidak hanya harus menghadapi stress beban studi melainkan juga harus mampu meng- hadapi proses akulturasi yang dilaluinya. Sebagian besar studi yang terdahulu masih tentang maha- siswa China atau Korea di Amerika atau mahasiswa asing, non-Indonesia. Karenanya studi ini ber- tujuan untuk eksplorasi variabel yang penting dalam akulturasi mahasiswa Indonesia di Jerman, dengan pendekatan kualitatif. Hasilnya menunjukkan bahwa variabel akulturasi yang penting ada- lah sebagai berikut: (1) musim dan cuaca, (2) tempat tinggal, (3) hubungan sosial saat “ini”, (4) ke- bersamaan dengan sesama orang Indonesia di Jerman, (5) penguasaan Bahasa Jerman, (6) peran dalam kerja atau akademik, dan (7) kebebasan. Detail didiskusikan dalam artikel ini.